2011
DOI: 10.1097/ico.0b013e3182031fec
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Interlamellar Stromal Keratitis After Laser In Situ Keratomileusis

Abstract: The authors report a case of a Descemet stripping automated endothelial keratoplasty that was complicated by intraoperative bleeding from the iridotomy site. Slit-lamp examination on postoperative day 1 revealed significant amount of retained blood at the donor-recipient interface and a best-corrected visual acuity (BCVA) of 20/400. The patient was managed with periodic observation and a topical fluoroquinolone and 1% prednisolone. By postoperative month 8, the interface had cleared, and the BCVA improved to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…3,5,17,18,19 Other possible interface abnormalities, such as blood, inflammatory or epithelial cells, metallic particles, calcareous degeneration, or retained Descemet membrane, have been reported. 11,17,[20][21][22][23] Although there have been a few small case series reporting an interface haze or opacity, this is the largest case series to describe the condition with its potential impact on visual outcomes. 18,19,[24][25][26][27] In this case series, there were no signs of inflammation, rejection, edema, or infiltrate in association with the interface opacity.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…3,5,17,18,19 Other possible interface abnormalities, such as blood, inflammatory or epithelial cells, metallic particles, calcareous degeneration, or retained Descemet membrane, have been reported. 11,17,[20][21][22][23] Although there have been a few small case series reporting an interface haze or opacity, this is the largest case series to describe the condition with its potential impact on visual outcomes. 18,19,[24][25][26][27] In this case series, there were no signs of inflammation, rejection, edema, or infiltrate in association with the interface opacity.…”
Section: Discussionmentioning
confidence: 92%
“…[3][4][5][6][7][8][9][10][11][12][13] We report a case series of 30 patients who developed varying degrees of interface opacity at the level of the graft-host interface after DSAEK. Although the exact etiology of this finding remains unknown, the study provides new valuable information regarding long-term visual outcomes and potential causes for the opacity, including retained viscoelastic and an irregular stromal surface of the donor tissue, with slightly different clinical presentations.…”
mentioning
confidence: 98%
“…Persistent blood in the graft-host interface may be associated with development of late corneal haze and a subsequent decrease in visual performance and acuity. Schmitt et al 8 recently reported a case with intraoperative interface bleeding from a peripheral iridotomy during DSEK. Repeated attempts were made to wash the interface during the surgery.…”
Section: Discussionmentioning
confidence: 96%
“…1,2 Complication rates in literature are variable and dependent on the experience of surgeons, patients' factors, and the surgical techniques used. [1][2][3][4][5][6][7][8] In a case file analysis of 118 patients undergoing DSEK, Suh et al reported a myriad of complications, including retinal detachment, cystoid macular edema, epithelial ingrowth, and retained blood, at the donor-host interface. 3 Other less commonly reported complications include lamellar disc and intraocular lens dislocation into the vitreous cavity, herpetic keratitis, retrocorneal fibrous membrane, and aqueous misdirection syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Previously described graft-host DSAEK interface complications include postoperative vascularization, sequestered blood, microbial keratitis, retained metallic particles, epithelial ingrowth, retained fragments of Descemet membrane, and calcareous degeneration. [1][2][3][4][5][6][7][8] We report a unique interface complication in an aniridic patient with a complicated ocular history including previous DSAEK under PKP, who underwent secondary placement of a Baerveldt glaucoma tube shunt. Postoperatively, the tube was found to be positioned in the DSAEK-PKP interface, requiring tube repositioning at the time of subsequent repeat PKP and placement of a Boston type I keratoprosthesis.…”
mentioning
confidence: 97%